ENVIRONMENTAL IMPACT OF THE TEXTILE INDUSTRY AND THEIR MITIGATION SOLUTIONS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
This article analyzes the negative impact of the textile industry on the environment, including water and air pollution, soil degradation, and the problem of solid waste. It also presents proposals and solutions for establishing environmentally sustainable production.